2022
DOI: 10.3389/fpls.2022.779830
|View full text |Cite
|
Sign up to set email alerts
|

Software Choice and Sequencing Coverage Can Impact Plastid Genome Assembly–A Case Study in the Narrow Endemic Calligonum bakuense

Abstract: Most plastid genome sequences are assembled from short-read whole-genome sequencing data, yet the impact that sequencing coverage and the choice of assembly software can have on the accuracy of the resulting assemblies is poorly understood. In this study, we test the impact of both factors on plastid genome assembly in the threatened and rare endemic shrub Calligonum bakuense. We aim to characterize the differences across plastid genome assemblies generated by different assembly software tools and levels of se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…It is probable that this duplication occurred because of the use of short reads and the De Bruin graph for sequence assembly 47 . Although GetOrganelle has demonstrated the highest accuracy among all published plastid assembly pipelines in benchmarks [48][49][50] , this observation underscores the importance of the molecular validation of in silico results.…”
Section: Mitochondrial Genome Assembly Challenges: Lessons From Ellob...mentioning
confidence: 89%
“…It is probable that this duplication occurred because of the use of short reads and the De Bruin graph for sequence assembly 47 . Although GetOrganelle has demonstrated the highest accuracy among all published plastid assembly pipelines in benchmarks [48][49][50] , this observation underscores the importance of the molecular validation of in silico results.…”
Section: Mitochondrial Genome Assembly Challenges: Lessons From Ellob...mentioning
confidence: 89%
“…Similarly, Freudenthal et al [30] used sequencing coverage as part of a special metric to evaluate the accuracy of plastid genome assemblies and found that this metric differed strongly between different plastome assembly software. Giorgashvili et al [31] tested the opposite association and reported that plastid genome assembly software tools generated different contigs depending on the levels of sequencing coverage. Hence, software choice most likely has a considerable impact on the results of plastome assembly, including its sequencing coverage [101], even if sequencing evenness may not be affected at a significant level.…”
Section: Sequencing Evenness and Software Choicementioning
confidence: 99%
“…However, the average plastome-wide sequencing depth is the only assembly quality metric that is somewhat frequently applied in contemporary plastid genomics. Twyford and Ness [29] discussed its use in identifying the overall adequacy of sequencing coverage in plastid genomics, while studies such as Freudenthal et al [30] and Giorgashvili et al [31] employed it to determine the accuracy of de novo plastid genome assemblies. Except for Gu et al [6], sequencing evenness has barely been used as a quality metric for plastid genome assemblies, even though the precise distribution of sequencing depth can help identify genome regions of inadequate coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the SDR refers to the ratio of each coting’s sequencing depth to the average sequencing depth of the organelle genome. Given that organelle genomes exist in multiple copies within a cell, they typically exhibit higher sequencing depths than nuclear genome(Sanita Lima et al, 2016;Wang et al, 2018;Li et al, 2021;Giorgashvili et al, 2022;Zhou et al, 2023a). Therefore, a contig with a high sequencing depth ratio, similar to the average of the organelle genome, is more likely to be a part of the organelle genome.…”
Section: Introductionmentioning
confidence: 99%